Kebangkitan Konservatisme Islam: Politik Identitas dan Potret Demokrasi di Indonesia - Pribadi, Yanwar (Studia Islamika, 2021)
Leonard C. Sebastian, Syafiq Hasyim and Alexander R. Arifianto (eds). 2021. Rising Islamic Conservatism in Indonesia: Islamic Groups and Identity Politics. London and New York: Routledge.This volume discusses the rise of Islamic conservatism in Indonesia that is opposed to the values of pluralism, tolerance, and religious freedom. The authors argue that Islamic conservatism presents an enormous challenge to Indonesia as a multi-religious country that adversely affects its social, cultural, and political situations. They are concerned that Islamic conservatism may distance Indonesia from religious inclusion, and in fact, it may bring the country closer to religious exclusion. They are also worried that religious intolerance is increasingly on the rise, as shown in the cases of the prohibition of the establishment of churches in Muslim neighbourhood, the abuse of the blasphemy law to punish minority groups, the establishment of exclusive ‘sharia’ housing complexes that is intended only for ‘like-minded’ Muslims, and vigilante-style persecutions such as threats, verbal harassment, and physical intimidation against people or groups who are opposed to the perpetrators’ religious views. In addition, the authors also emphasize that there is an ongoing movement among supporters of Islamic conservatism to signify their religious boundaries and at the same time reject those who do not follow their path.